A STUDY ON PARTICLE SWARM OPTIMIZATION WITH APPLICATION - (NIM: 20107015), IRIANTO
Nature has inspired many scientists and researchers to develop new knowledge and understanding. One of them is about the social behavior of animals that live in groups. Particle swarm optimization is one method that inspired by the behavior of animals in groups. Particle swarm optimization or known as PSO assigns some behavior of every individual in the whole swarm, and then combine that behavior to solve problems. Since its introduction in 1995, many scientists and researchers have developed the algorithm. One of the PSO applications is in optimal control problems. Optimal control problems solved in this thesis is fixed time and fix end point case one. They are hard to solve for the exact solutions. This thesis shows that PSO can be used and is a powerful algorithm to solve optimal control problems. At the end of this thesis it is shown that PSO gives a good solution to the optimal control problems.